Controls on soil respiration in alpine tundra - Schliemann, Sarah A.; Grevstad, Nels; Parr, David A. (Geoderma Regional, 2025)
Alpine tundra ecosystems, like their arctic counterparts, have historically been the sites of considerable soil organic carbon (SOC) storage due to climatic factors that suppressed microbial activity. While climatic factors are important, heterotopic soil respiration (and SOC storage) may be influenced by a range of soil characteristics. In this study, we measured soil respiration, soil temperature, soil moisture, soil nutrient concentrations, soil pH, and soil texture in 4 alpine tundra sites located in Rocky Mountain National Park, Colorado, USA from June 2015 – September 2021. We also used geospatial modeling to visualize predicted climate changes in this system over the 21st century. Finally, we measured SOC concentrations over the seven-year study. We found that soil respiration was significantly correlated with soil temperature, soil moisture, and soil texture. All other parameters were not significantly correlated with soil respiration. We also found that SOC concentrations did not change significantly over the course of the seven-year study. The predictive models show that by the end of the century, over the majority of the park, the mean maximum air temperature will increase, the amount of snowfall will decrease, soil moisture will decrease, and the number of snow-free days will increase. These results suggest that SOC is not currently being lost from this system at a high rate. In addition, it appears that with a changing climate, soil respiration may increase with warming, but the overall increase may be limited by decreased soil moisture and in some cases, high soil temperatures. •Soil respiration was related to soil temperature and soil moisture, increasing and then decreasing as soil temperatures varied from 0 to 18 °C, and increasing as soil moisture varied from 0 to 100 %.•Soil respiration was unrelated to soil nutrient concentrations or soil pH.•Soil organic carbon (SOC) concentrations did not change significantly over the seven-year study.